Supreme Court Policy On Underage Marriage Dispensation Realizing Legal Certainty - Woro Mega Dwi Astuti; Jacinda Ilma Mayastika; Dian Latifiani (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
The issuance of Law Number 16 of 2019, Amendments to Law Number 1 of 1974 on Marriage, has given Indonesia a new perspective on the law of marriage. The Supreme Court has issued Supreme Court regulation of Republic Indonesia Number 5 of 2019 concerning adjudicating application guidelines for Marriage Dispensation. The study employed normative research. The findings showed that Supreme Court Regulation Number 5 of 2019 is a special rule made by the Supreme Court to explain the procedural law, applying for marriage dispensation, which has not been clearly regulated in Article 7 of Law Number 16 of 2019. One way to overcome marriage dispensation-related problems is by creating limited rules. Particularly, the reasons for filing such cases. The responsible law enforcers are also expected to tighten the application procedure. Thus,  the number of early marriages can be lessened.